Bài tổng quan: Năng lượng cho thế kỷ 21. - Trí, Trần Mạnh (Vietnam Journal of Chemistry, 2012)
Energy is of paramount importance for a modern economy. In the last century, world energy supply was mainly based on fossil fuels - coal, oil and natural gas, provided over 80% of the energy required today. However, the high reliance on the use of fossil fuels contributes directly to polluting of the environment and increasing levels of greenhouse gases in the atmosphere. Climate change is the greatest challenge face the humanity at the start of 21st century. Morover, their limited reserves insufficient supply to meet the increasing demands for energy, it is essential to introduce alternative sources of energy: the renewable one. The most promising of these energies are wind, hydro (large and small), solar, geothermal, biomass and hydrogen energies. The renewable energy sources are essentially carbon-free and appear to be generally more suitainable than fossil fuels and could provide a major proportional the world’s needs by the middle of the 21st century. The introduction of renewable energy sources in the world’s energy balance can reduce CO2 emission, cut energy cost, avoid energy crisis. In addition, the Carbon Capture and Storage (CCS) as well as the carbon Capture and Conversion (CCC) technologies, the taxation of CO2 emission would generate strong incentives for a low-carbon transition in the 21st century. The rapid development and deployment of low-carbon technologies is vital to climate change mitigation. In conclusion the renewable energy sources are likely to play a greatly-increased role in the future energy supplies with zero-carbon emission, there will be the ultimate change from non-renewable energy to renewable energy as an energy revolution and innovation of century.